The Dynamics of Conservatism in Halal Certification, Sharia Regional Regulations, and Moral Regulation: A Study of Islamic Legal Policy in Indonesia - Arifin, Bustanul; Moh. Ulumuddin; Ansori, Ahmad Insya (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2025)
Background. Holistic and interconnected studies on halal certification, sharia regulations, and moral regulations as real manifestations of the conservative movement in Indonesian Islamic legal policy are still limited. Aim. This article examines the dynamics of conservatism in Islamic legal policy in Indonesia, focusing on halal certification, sharia-based local regulations (sharia regional regulations), and moral regulation. The central issue addressed is how conservative movements influence the formulation and implementation of Islamic legal policies at both national and local levels. Method. This study employs a library research method with a descriptive qualitative approach, analyzing academic literature, legal documents, and relevant empirical data. Result. The findings reveal that halal certification, sharia regulations, and moral policies serve not only as instruments of religious and consumer protection, but also as tools for social control, economic selection, and consolidation of majority identity politics. However, these policies present challenges such as unequal access, potential discrimination against minorities, and the narrowing of civil liberties. The study underscores the importance of developing fair, inclusive, and dialogical Islamic legal policies to promote social cohesion and justice within a multicultural society.